Appendicitis versus non-specific acute abdominal pain: Paediatric Appendicitis Score evaluation - Marcos Prada Arias; Angel Salgado Barreira; Margarita Montero Sánchez; Pilar Fernández Eire; Silvia García Saavedra; Javier Gómez Veiras; José Ramón Fernández Lorenzo (Elsevier, 2018)
Introduction: Non-specific acute abdominal pain is the most common process requiring differential diagnosis with appendicitis in clinical practice. The aim of this study was to assess the Paediatric Appendicitis Score in differentiating between these two entities. Material and methods: All patients admitted due to suspicion of appendicitis were prospectively evaluated in our hospital over a two-year period. Cases of non-specific acute abdominal pain and appendicitis were enrolled in the study. Several variables were collected, including Score variables and C-reactive protein levels. Descriptive, univariate and multivariate analyses and diagnostic accuracy studies (ROC curves) were performed. Results: A total of 275 patients were studied, in which there were 143 cases of non-specific acute abdominal pain and 132 cases of appendicitis. Temperature and right iliac fossa tenderness on palpation were the variables without statistically significant differences, and with no discrimination power between groups. Pain on coughing, hopping, and/or percussion tenderness in the right lower quadrant was the variable with greater association with appendicitis. The Score correctly stratified the patients into risk groups. Substitution of temperature for C-reactive protein in the Score increased diagnostic accuracy, although with no statistically significant differences. Conclusions: The Paediatric Appendicitis Score helps in differential diagnosis between appendicitis and non-specific acute abdominal pain. It would be advisable to replace the temperature in the Score, since it has no discrimination power between these groups. C-reactive protein at a cut-off value of 25.5 mg/L value could be used instead. Resumen: Introducción: El dolor abdominal agudo inespecífico es el principal proceso que requiere diagnóstico diferencial con la apendicitis en la práctica clínica. El objetivo de este estudio es evaluar la utilidad del Pediatric Appendicitis Score (Regla de predicción clínica de apendicitis pediátrica) para diferenciar estas 2 entidades. Material y métodos: Se evaluó prospectivamente a los pacientes atendidos por sospecha de apendicitis en nuestro centro durante 2 años, incorporando al estudio casos de dolor abdominal agudo inespecífico y apendicitis. Se recogieron diferentes variables, incluyendo las que conforman el Score y la proteína C reactiva, que se analizaron estadísticamente de manera descriptiva, univariante y multivariante, y mediante pruebas de rendimiento diagnóstico (curvas ROC). Resultados: Se estudiaron 275 casos; 143 casos de dolor abdominal agudo inespecífico y 132 casos de apendicitis. La temperatura y el dolor a palpación en fosa iliaca derecha fueron las únicas variables que no mostraron diferencias significativas entre los grupos, careciendo de poder de discriminación. El dolor con la tos, el salto y/o la percusión fue la variable con mayor asociación a apendicitis. El Score estratificó correctamente a los pacientes en grupos de riesgo. La sustitución de la temperatura por la proteína C reactiva en el Score aumentaba su rendimiento diagnóstico, aunque sin diferencias significativas. Conclusiones: El Pediatric Appendicitis Score ayuda en el diagnóstico diferencial entre apendicitis y dolor abdominal agudo inespecífico. Sería recomendable la sustitución de la temperatura en el Score, pues carece de poder de discriminación entre estos grupos. La proteína C reactiva, categorizada en el valor 25,5 mg/L, podría ser utilizada en su lugar.